Looking closely at teachers who prepare for museum visits - Mosabala, Mpho Shadrack (My University, 2009)
Although other research has addressed some features of successful school group visits to museums, such as preparation and follow up and emphasis on first-hand experience, there has been little research on the practices being used by the teachers who take their classes to the museums. I examined how teachers from five schools conducted their visits to one of four museums (Scibono Discovery Centre, HartRAO, Johannesburg Planetarium or Adler Museum) with their learners. The case study involved observing the five teachers before, during and after the visit and interviewing them before and after the visit. The data were analysed using communities of practice theory to determine the practices of the selected teachers. An in-depth analysis of the five teachers’ interviews and observations was done both for the rich data it provided and for triangulation purposes. The analysis shows that three teachers had what was described as task-oriented preparation while the other two had learning-oriented preparation. One teacher preparation was also described as not directly about the visit. The analysis further shows that four teachers were observed to have no interaction with their learners in some instance. Three teachers had learning oriented interaction with their learners at the museums. Three teachers were also observed controlling the behaviour of their learners. Furthermore, the analysis shows that the purposes and objectives of the field trips as given by teachers were for entertainment, edutainment,curriculum, interactive, career and tradition. Lastly, teachers follow up activities were described as either task-oriented or learning-oriented. The study shows that some teachers are old timers while others are newcomers in the community of teachers who take their classes to the museums.
Keywords: Museum; Field trip; Communities of Practice; Legitimate Peripheral Participation; Informal learning; School visits